On Regional Co-Operation and Low- Cost Investment Enclaves: An Empirical Study on Singapore's Industrial Parks in Riau, Indonesia - YEOH, Caroline (Institutional Knowledge at Singapore Management University, 2003)
Infrastructure can be unreliable and administration subject to corruption in Asia's rapidly developing economies. Foreign investment is thus drawn to privileged investment enclaves, as well as in and around centers of international infrastructure. This context provides opportunity for Singapore-styled industrial parks, through the provision of superior infrastructure, the ability to negotiate investment concessions at inter-government level and, where existing, through the links to influential Chinese business groups in the investment location. Batamindo Industrial Park and Bintan Industrial Estate in Indonesia were the prototypes. This paper revisits the Parks, and offers a stock-take on the challenges confronting these flagship projects. Evidence from on-site surveys and interviews are presented. This paper concludes that the raison d'etre for the projects has overestimated the attractiveness of the low-cost investment enclaves for multinational companies, and the projects' potential has been largely overshadowed by socio-political uncertainties in the host environment.